Republic of Belarus - Deposit Insurance : Technical Note - World Bank (Washington, DC : World Bank, 2022)
The current system of deposit insurance is governed by two different pieces of legislation, each in turn elaborated by a separate National Bank of Belarus (NBB) resolution. The two legislations cover foreign exchange accounts in state owned banks and all other accounts, respectively. The first legislation was the presidential decree of April 20, 1998, which established full coverage for foreign exchange accounts in six state banks. The second legislation is Article 121 of the Banking Code which is the legal basis for coverage for all other deposits and which became effective October 12, 2000. The deposit insurance system is currently characterized by preferential treatment of the authorized banks and in particular Belarusbank and Belagroprombank.